Relaxin‐3 inputs target hippocampal interneurons and deletion of hilar relaxin‐3 receptors in "floxed‐RXFP3" mice impairs spatial memory. Issue 5 (31st January 2017) - Haidar, M.; Guèvremont, G.; Zhang, C.; Bathgate, R.A.D.; Timofeeva, E.; Smith, C.M.; Gundlach, A.L.
ABSTRACT: Hippocampus is innervated by γ‐aminobutyric acid (GABA) "projection" neurons of the nucleus incertus (NI), including a population expressing the neuropeptide, relaxin‐3 (RLN3). In studies aimed at gaining an understanding of the role of RLN3 signaling in hippocampus via its Gi/o ‐protein‐coupled receptor, RXFP3, we examined the distribution of RLN3‐immunoreactive nerve fibres and RXFP3 mRNA‐positive neurons in relation to hippocampal GABA neuron populations. RLN3‐positive elements were detected in close‐apposition with a substantial population of somatostatin (SST)‐ and GABA‐immunoreactive neurons, and a smaller population of parvalbumin‐ and calretinin‐immunoreactive neurons in different hippocampal areas, consistent with the relative distribution patterns of RXFP3 mRNA and these marker transcripts. In light of the functional importance of the dentate gyrus (DG) hilus in learning and memory, and our anatomical data, we examined the possible influence of RLN3/RXFP3 signaling in this region on spatial memory. Using viral‐based Cre/ LoxP recombination methods and adult mice with a floxed Rxfp3 gene, we deleted Rxfp3 from DG hilar neurons and assessed spatial memory performance and affective behaviors. Following infusions of an AAV (1/2) ‐Cre‐IRES‐eGFP vector, Cre expression was observed in DG hilar neurons, including SST‐positive cells, and in situ hybridization histochemistry for RXFP3 mRNA confirmed receptor depletion relative to levels in floxed‐RXFP3 mice infused with an AAV (1/2) ‐eGFP (control) vector. RXFP3 depletion within the DG hilus impaired spatial reference memory in an appetitive T‐maze task reflected by a reduced percentage of correct choices and increased time to meet criteria, relative to control. In a continuous spontaneous alternation Y‐maze task, RXFP3‐depleted mice made fewer alternations in the first minute, suggesting impairment of spatial working memory. However, RXFP3‐depleted and control mice displayed similar locomotor activity, anxiety‐like behavior in light/dark box and elevated‐plus maze tests, and learning and long‐term memory retention in the Morris water maze. These data indicate endogenous RLN3/RXFP3 signaling can modulate hippocampal‐dependent spatial reference and working memory via effects on SST interneurons, and further our knowledge of hippocampal cognitive processing. © 2017 Wiley Periodicals, Inc.